(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
English is the language that the world uses most extensively nowadays. More and more Indian know the importance of English learning. By Learning English well, we can understand more information of outside world. Environment is considered a complex set of physical, geographical, biological, social, cultural and political conditions that surrounds an individual and determines his performance. The school environment is the result of the interaction of teachers- students’ relationship, teachers’ academic and professional qualification, teachers’ teaching. School environment if the sum of all physical, emotional, social, mental, organizational and instructional factors that contribute to the total teaching learning process with in school having maximum influence on the quality and quantity of students teachers actions and has also facilitating effects on eh achievement of students. The purpose of this paper is to study the influence of the environment factors on English learning. They can help English learners to study English better and improve their English in India.